Optineurin overexpression ameliorates neurodegeneration through regulating neuroinflammation and mitochondrial quality in a murine model of amyotrophic lateral sclerosis - Zhao, Shumin; Chen, Ranran; An, Yi; Zhang, Yali; Ma, Cheng; Gao, Ying; Lu, Yanchao; Yang, Fei; Bai, Xue; Zhang, Jingjing (Frontiers in Aging Neuroscience, 2025)
IntroductionAmyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by the loss of motor neurons (MNs). Genetic mutations in Optineurin (OPTN) and Superoxide Dismutase 1 (SOD1) have been identified as causal factors for ALS. OPTN immunopositive inclusions have been confirmed in the cases of ALS with SOD1 mutations. However, the role of the OPTN gene in ALS caused by SOD1 mutations is ambiguous.MethodsThe murine Optn lentivirus and empty vector lentivirus were injected into SOD1G93A mice after discovering variations in Optn expression over time. The phenotype onset date, life span, locomotor activity, and pathological changes in the spinal cord were determined and recorded subsequently. In addition, the influences on cellular apoptosis, mitochondrial dynamics, mitophagy, and neuroinflammation were further investigated.ResultsOptn expression was increased in the spinal cord of SOD1G93A mice at the pre-symptomatic phase, but decreased after disease onset. Optn overexpression led to a 9.7% delay in the onset of disease and improved motor performance in SOD1G93A mice. Optn overexpression also ameliorated the MNs loss by 46.8%. Moreover, all these ameliorating effects induced by Optn overexpression might be due to the inhibition of cellular apoptosis, improvement of mitochondrial quality, regulation of mitochondrial dynamics, promotion of mitophagy, and anti-inflammatory properties.ConclusionOur data demonstrate that Optn overexpression protects MNs, inhibites cellular apoptosis, improves mitochondrial quality and regulates neuroinflamation in SOD1G93A mice at the pre-symptomatic stage.